2018
DOI: 10.1177/1468794118781718
|View full text |Cite
|
Sign up to set email alerts
|

Putting graphic elicitation into practice: tools and typologies for the use of participant-led diagrams in qualitative research interviews

Abstract: The use of diagrams to stimulate dialogue in research interviews, a technique known as graphic elicitation, has burgeoned since the year 2000. Reviews of the graphic elicitation literature have relied on the inconsistent terminology currently used to index visual methods, and have so far drawn only a partial picture of their use. Individual diagrams are seen as stand-alone tools, often linked to particular disciplines, rather than as images created from a toolbox of common elements which can be customized to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 69 publications
0
44
0
1
Order By: Relevance
“…Notably, several authors have suggested that the use of visual techniques (e.g., expressive drawing, picture completion, diagram construction) can help interviewees elaborate further their thoughts on interview topics (Bravington & King, 2019; Comi et al, 2014). For Comi et al (2014), using visuals during interviews, both as projection and facilitation techniques, has a number of benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, several authors have suggested that the use of visual techniques (e.g., expressive drawing, picture completion, diagram construction) can help interviewees elaborate further their thoughts on interview topics (Bravington & King, 2019; Comi et al, 2014). For Comi et al (2014), using visuals during interviews, both as projection and facilitation techniques, has a number of benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, visual data used and/or produced during interviews—in combination with verbal interpretations produced by the interviewees—can foster the elicitation of tacit knowledge, and act as a knowledge repository (Comi et al, 2014). The use of artefacts such as organization charts, timelines, and others diagrams in interviews can also improve recall and stimulate meaning making (Bravington & King, 2019). Interviewers may bring their own visuals to an interview or ask interviewees to engage in drawing, or other construction exercises to represent their situation or some object relevant to the study.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our study ethos, we wanted to use visual methods within this study, as graphic elicitation is a valuable method to uncover the intricacies of lived experience that might not come to light through discussion alone, particularly when exploring sensitive issues ( Aarsand & Aarsand, 2018 ; Bravington & King, 2018 ; Cornwall, 1992 ; Gauntlett, 2007 ; Rose, 2007 ). Qualitative studies have used an array of visual methods for more creative interviewing methods including photographs ( Frith & Harcourt, 2007 ; Heng, 2017 ; Radley & Taylor, 2003 ; Rose, 2007 , 2012 ), Lego ( Gauntlett, 2007 ), paintings and artwork ( Irving, 2007 ), possessions in the home ( Grant et al, 2017 ; Miller, 2008 ), and sandboxing ( Mannay et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 Qualitative, arts-based methods have been shown to be helpful in facilitating self-expression of experiences, feelings, and perceptions not easily articulated by words. 1 , 30 Arts-based methods like photovoice that capture personally significant experiences 31 – 33 and/or ecomaps that display the nature of networks 34 , 35 provide insight into the lived experience, contributing to the qualitative design of hermeneutic phenomenology. This methodology is a powerful strategy for accessing youths’ conscious and unconscious feelings about difficult life situations, 31 , 36 38 such as misdiagnosis, stigma, and/or under-treatment.…”
Section: Introductionmentioning
confidence: 99%